Terrorism versus insurgency: a conceptual analysis - Ünal, Mustafa Cosar (Crime, law and social change, 2016)
This study analyzes the distinction between terrorism and insurgency by drawing upon the case of the PKK conflict in Turkey. It provides a conceptual discussion through multi-dimensional analyses from the actor-oriented, the action-oriented, the purpose-oriented, and the ontology-oriented perspectives. In so doing, in addition to the organizational characteristics, it critically identifies the PKK’s varying strategies of terrorist and insurgent violence, and their temporality and reasoning as the conflict unfolded to make conceptual inferences. This study found, first, that while the PKK as an actor indicates an insurgent character, the PKK’s use of violence reflects intense terrorism action particularly after its military defeat. Second, the use of terrorism by the PKK reflects an inextricable overlap in temporality and a direct link with guerilla methods. Despite the PKK’s terrorist and insurgent violence resulted from different factors and reasoning at the intermediate level; they are designed to converge at the overall aim of the PKK’s political campaign. Third, the PKK violence reflects varying purposes of terrorism, e.g., intimidation, attrition, survival and group solidarity. Fourth, after reaching the tipping point that resulted in its military defeat in 1994, the PKK resorted to more indirect and asymmetrical violence in an increasing tendency to deflect state power and, thus, to coerce Turkey into a political compromise, i.e., a negotiated settlement.